Effect of nutrient management interventions on system productivity of rice-ragi sequence in Coastal Andhra Pradesh - Kumar, S Kiran; Rao, Ch Pulla; Murthy, VRK; Rani, Y Ashoka; Prasad, PRK; Kumar, R Mahender (ORYZA-An International Journal of Rice, 2020)
A field experiment was conducted during kharif season of 2017 & 2018 and rabi season of 2017-18 and 2018-19 on sandy loam soil of the Agricultural College Farm, Bapatla to evaluate the system productivity of rice- no till ragi cropping system with seven treatments in kharif and in rabi season each kharif treatment divided into four sub treatments. The experiment consisted of seven treatments viz., T1 : 100% RDF (100-60-40 N-P-K kg ha-1) ; T2: 100% RDF + soil application of ZnSO4 @ 50 kg ha-1 ; T3: 125% RDF + soil application of ZnSO4 @ 50 kg ha-1; T4: 75% RDF + poultry manure @ 0.82 t ha-1 + soil application of ZnSO4 @ 50 kg ha-1; T5: 75% RDF + FYM @ 5.0 t ha-1 + soil application of ZnSO4 @ 50 kg ha-1; T6: 50% RDF + poultry manure @1.6 t ha-1 + soil application of ZnSO4 @ 50kg ha-1 and T7: 50% RDF + FYM @ 10 t ha-1 + soil application of ZnSO4@ 50 kg ha-1. The experiment was laid out in Randomized Block Design and replicated thrice during kharif rice and in rabi four sub treatments i.e, S1:No fertilizer, S2:100% RDF (30-30-20 N-P-K kg ha-1), S3:75% RDF (22.5-22.5-15 NP-K kg ha-1) and S4:50% RDF (15-15-10 N-P-K kg ha-1) and hence, split plot design was adopted. Maximum rice equivalent yield of ragi (8108, 8570 and 8339 kg ha-1 in both the years and in pooled data respectively) as well as system productivity of rice-ragi (13452, 14036 and 13744 kg ha-1 in both the years and in pooled data respectively) sequence was observed with 50% RDF + FYM @ 10 t ha-1 + ZnSO4 @ 50 kg ha-1 as residual effect, among the fertilizer levels, S2 level i.e., 100 % RDF (30-30-20 kg N-P-K ha-1) on succeeding ragi crop (7413, 8003,7708 and 11893,12641, 12267 kg ha-1 rice equivalent yield and system productivity respectively in both the years and in pooled data).